Charge‐Transfer Magnets: Multiferroicity of Carbon‐Based Charge‐Transfer Magnets (Adv. Mater. 4/2015). (January 2015) - Qin, Wei; Gong, Maogang; Chen, Xiaomin; Shastry, Tejas A.; Sakidja, Ridwan; Yuan, Guoliang; Hersam, Mark C.; Wuttig, Manfred; Ren, Shenqiang
<x xml:space="preserve">Abstract</x> Carbon charge‐transfer complexes offer great potential for next generation organic multiferroics. On page 734, S. Ren and co‐workers demonstrate room temperature magnetoelectric coupling of nanocarbon charge‐transfer magnets. In the image magnetic field effects on optoelectronic and dipole properties of nanocarbon complexes are shown, which would be critical for the development of all‐organic multifunctional smart devices. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>